El poder de la prensa, la prensa del poder : reflexión entorno al periodismo afroargentino - Jean Arsène Yao (Amnis)
In the 1850's appeared an Afro-Argentinian activist press, which defended the black community interests. In this paper the author tries to evaluate if the Argentinians of African origin realized the full power of the written press as a way of spreading their ideas.Therefore, he explains the conversion of the Afro-Argentinians newspapers as political instruments.